MEDICAL, BIOLOGICAL AND TOXICOLOGICAL ASSESSMENT OF USING BIO-PREPARATIONS IN ARABLE FARMING - Pysarenko, P. V.; Samoilik, M. S.; Dychenko, O. Yu.; Sereda, M. S.; Poghosyan, A. А. (Scientific Progress & Innovations, 2021)
At present, the problem of utilizing a large amount of mineralized stratum water is rather important for Ukraine, on the whole, and Poltava region, in particular as getting much stratum water into the soil results in its considerable salinity, deterioration of structure and destruction of vegetation. An acute necessity arises in studying toxicological properties of mineralized stratum water, which will enable to determine the class of its danger and develop measures for safe using this preparation to eco-balance arable farming. That is why, for the first time, the assessment of eco-toxicological properties of mineralized stratum water as environmen-tally friendly substitute of agro-chemicals was conducted in our paper. According to the research results, it has been established that mineralized stratum water (MSW) is a low-toxic combination. LD50 of white female rats at oral intake made more than 21,000 mg/kg, female mice – 31,000 mg/kg, male mice – more than 20,000 mg/kg; at putting it on rats’ skin – more than 8,000 mg/kg. LD50 value at inhaling the substance made more than 5,000 mg/kg for female rats. It has been substantiated that in accordance with 12.1.007-76 State Standard, mineralized stratum water belongs to the IVth class of danger at oral taking and getting through the skin, and to the IIId class at inhaling.. It has also been determined that mineralized stratum water does not have irritating effect on the skin and eye mucosa. No sensitizing effect was detected on the organism of guinea pigs. The studies have shown that cumulative properties of mineralized stratum water are weakly ex-pressed. Cumulative coefficient is more than 5. In the dose of 4,260 mg/kg, mineralized stratum water has cardio toxic effect, causes erothropoesis, increases kidneys’ filtration and excretion functions. 2,130 mg/kg was inactive dose for rats in sub-chronic experiment. The obtained results of eco-toxicological analyzing mineralized stratum water enable to maintain that its using is safe enough in arable farming system, in par-ticular, as environmentally safe organic and mineral fertilizer, herbicide and fungicide.